Analysis of dietary pattern effects on metabolic risk factors using structural equation modeling - Moe, Åse Mari; Sørbye, Sigrunn H. (Frontiers in Nutrition, 2025)
BackgroundThis study aimed to investigate the effects of dietary patterns on metabolic cardiovascular disease (CVD) risk factors in a Nordic population.MethodsThe study sample comprised 9,988 participants aged 40–79 years from the seventh Tromsø study (Norway). Available data included food intake values collected by a food frequency questionnaire. Exploratory structural equation models were utilized to analyse direct, indirect, and total effects of dietary patterns on metabolic CVD risk factors, using obesity as a mediator. The CVD risk factors included CRP, HDL-cholesterol, triglycerides, glycated hemoglobin, and blood pressure. All structural equations were adjusted for available lifestyle and demographic variables.ResultsThree common dietary patterns for women and men were identified, named Snacks and Meat, Health-conscious, and a Processed Dinner pattern. Additionally, a Porridge pattern was identified for women and a Cake pattern for men. The Health-conscious pattern showed a direct favorable effect on HDL-cholesterol (both sexes) and triglycerides (women). The Snacks and Meat pattern showed an unfavorable direct effect on triglycerides (men), while the Cake pattern had a favorable effect. All patterns, except the Health-conscious pattern for women, had direct effects on obesity, indirect effects on all metabolic risk factors, and a total effect on CRP. Snacks and Meat and the Processed Dinner patterns had unfavorable total effects on HDL-cholesterol (both sexes).ConclusionDietary patterns showed direct associations with HDL-cholesterol and triglycerides. Obesity was an important mediator in explaining the indirect effects of dietary patterns on all metabolic risk factors.